DETERMINANTS OF THE P/B RATIO IN THE COSMETIC SUBSECTOR IN INDONESIA - Chandra, Dicky (Finansha: Journal of Sharia Financial Management, 2024)
The cosmetics industry in Indonesia has seen significant growth in recent years, driven by high competition, rapid consumer trend shifts, and the need for constant product innovation. This study aims to analyze the effects of capital structure, profitability, and firm size on the Price to Book Ratio (P/B Ratio) of companies in Indonesia's cosmetics subsector. Using a quantitative approach with a descriptive-verificative analysis, the study population includes 10 cosmetics companies listed on the Indonesia Sharia Stock Index (ISSI) from 2021 to 2023, utilizing a saturated sample. Data were collected from each company's annual financial reports, focusing on variables such as Debt to Equity Ratio (DER), Return on Assets (ROA), and total assets as indicators of capital structure, profitability, and firm size, respectively. Multiple linear regression analysis was conducted to determine the impact of these financial metrics on firm value. The findings show that capital structure (DER) and profitability (ROA) positively and significantly affect the P/B Ratio, while firm size has no significant impact. These results imply that cosmetics companies should focus on managing debt strategically and improving profitability to enhance market valuation, as investors prioritize financial health and adaptability over sheer size.